Influence of the type of measuring device in determining the static modulus of elasticity of concrete - Araújo,S. S. (2012)
This paper presents a comparative analysis of the results obtained in static modulus of elasticity tests of plain concrete cylindrical specimens. The purpose of this study is to identify and evaluate the influence of several factors involved in modulus of elasticity tests such as the strain measurement device used (dial indicators, electrical surface bonded strain gages, externally fixed strain gages and linear variation displacement transducer - LVDT), the type of concrete (Class C30 and Class C60) and cylindrical specimen size (100 mm x 200 mm and 150 mm x 300 mm). The modulus tests were done in two different laboratories in the Goiânia, GO region and were performed according to code ABNT NBR 8522:2008, which describes the initial tangent modulus test, characterized by strains measured at tension values of 0.5 MPa and 30% of the ultimate load. One hundred and sixty specimens were tested with statistically satisfactory results. It was concluded that the type of strain measurement device greatly influenced the modulus of elasticity results. Tests in specimens 100 mm x 200 mm showed highest statistical variation.